The exploration for and possible genesis of, some Archaean granite/gneiss-hosted gold deposits in the Pietersburg granite-greenstone terrane - Linklater, Michael Anthony Leonard Flanders (Rhodes University, Faculty of Science, Department of Geology, 1992)
Abstract The gold mineralization event within Archaean granite-greenstone terranes occurred during the late Archaean, and followed the intrusion of syn- to late-tectonic granitic plutons into previously deformed greenstone belts. An Archaean granite/gneiss-hosted gold deposit, in terms of this project, is classified as having a gold-assay cutoff of 1g/metric ton over widths of at least several metres, or higher grades over narrower widths and/or verbal descriptions that indicate such values. Fluid inclusion studies and isotopic data identify two possible origins for the auriferous fluids; namely magmatic and metamorphic. The exploration target according to the magmatic model, is a late-Archaean, hydrothermally altered, mineralized and fractured granitic intrusion preferably with a granodioritic or quartz-dioritic composition. The exploration target according to the metamorphic replacement model is a granitic stock that has intruded a zone of crustal weakness such as a shear zone, active during the late Archaean. Alternatively, the granitic intrusion should be affected by regionally extensive late-Archaean shearing. It should be hydrothermally altered, deformed and mineralized. Five areas within the Pietersburg granite-greenstone terrane were selected for the 'Regional Area Selection' phase of exploration for Archaean granite/gneiss-hosted gold deposits; namely Roodepoort, Waterval, Ramagoep, Moletsie and Matlala. Roodepoort contains a known granodiorite-hosted gold deposit; the Knight's Pluton, and served as an orientation survey for this project. The use and interpretation of LANDSAT images formed an integral part of exploration techniques; to assess their usefulness in the exploration of Archaean granite/gneiss-hosted gold deposits. Area selection criteria for granite/gneiss-hosted gold mineralization at Roodepoort are the major ENE-trending shear zone, the NNW-trending lineament and hydrothermal alteration, shearing, quartz-stockworks and sulphide mineralization within the Knight's Pluton. The origin of the gold within the Knight's Pluton is uncertain; both magmatic and metamorphic models are possibilities. Ongoing exploration is in progress at Roodepoort. The only area selection criterion for granite/gneiss-hosted gold mineralization at Waterval is the sericitized, subcropping granites located within trenches. Gold mineralization is insignificant. No area selection criteria for Archaean granite/gneiss-hosted gold mineralization were located at Ramagoep, Matlala and Moletsie. No further exploration is recommended for all these areas. The MES image interpretations were successful in identifying lineaments, granitic outcrops, greenstones, vegetation and soil cover. The Clay-iron images adequately differentiated betweeen iron-rich and clay-bearing areas. However, not all clay-bearing areas were associated with hydrothermal alteratian; field checks were necessary to discriminate between weathered granites and hydrothermally altered granites. The Wallis images served to locally enhance the contrasts of the MES and Clay-iron images.
Keywords: Gold ores -- Geology -- South Africa; Gneiss; Granite